2011
DOI: 10.1107/s1600536811000377
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-3-[4-(Dimethylamino)phenyl]-1-(4-fluorophenyl)prop-2-en-1-one

Abstract: The mean planes of the two benzene rings in the title compound, C17H16FNO, are twisted slightly, making a dihedral angle of 7.8 (1)°. The prop-2-en-1-one group is also twisted slightly with a C—C—C—O torsion angle of −11.6 (3)°. In the crystal, weak inter­molecular C—H⋯O inter­actions link pairs of mol­ecules, forming centrosymmetric dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
2
7
0
Order By: Relevance
“…The mean plane of the prop-2-en-1-one group, the active site in this molecule, makes angles of 3.6 (0)° and 2.6 (7)°, respectively, with the hydroxyphenyl and dimethoxyphenyl rings. Bond lengths and angles are normal (Allen et al, 1987) and corespond to those observed in related compounds (Butcher et al, 2006;Cao et al, 2005;Harrison et al, 2007;Jasinski et al, 2010Jasinski et al, , 2011aJasinski et al, , 2011bNgaini et al, 2009;Radha Krishna et al, 2005;Sharma et al, 1997;Wu et al, 2005). (Table 1) and π-π stacking interactions (Table 2, Fig.…”
Section: S1 Commentsupporting
confidence: 62%
See 2 more Smart Citations
“…The mean plane of the prop-2-en-1-one group, the active site in this molecule, makes angles of 3.6 (0)° and 2.6 (7)°, respectively, with the hydroxyphenyl and dimethoxyphenyl rings. Bond lengths and angles are normal (Allen et al, 1987) and corespond to those observed in related compounds (Butcher et al, 2006;Cao et al, 2005;Harrison et al, 2007;Jasinski et al, 2010Jasinski et al, , 2011aJasinski et al, , 2011bNgaini et al, 2009;Radha Krishna et al, 2005;Sharma et al, 1997;Wu et al, 2005). (Table 1) and π-π stacking interactions (Table 2, Fig.…”
Section: S1 Commentsupporting
confidence: 62%
“…In continuation to our studies on crystal structures of chalcones (Jasinski et al, 2010(Jasinski et al, , 2011a(Jasinski et al, , 2011b, we report here the synthesis ( Fig. 1) and crystal structure of a new chalcone, C 17 H 16 O 4 , (I).…”
Section: S1 Commentmentioning
confidence: 70%
See 1 more Smart Citation
“…In continuation to our studies on crystal structures of chalcones (Jasinski et al, 2010(Jasinski et al, , 2011a(Jasinski et al, , 2011b, we report here the synthesis, Fig. 1, and crystal structure of a new chalcone, (I), Fig.…”
Section: S1 Commentmentioning
confidence: 71%
“…For related chalcone structures, see: Butcher et al (2006); Cao et al (2005); Harrison et al (2007); Jasinski et al (2010Jasinski et al ( , 2011a; Ngaini et al (2009); Radha Krishna et al (2005); Sharma et al (1997); Wu et al (2005) Experimental (16) 147Symmetry codes: (i) x À 1 2 ; Ày þ 1 2 ; Àz þ 1; (ii) Àx þ 1; y À 1 2 ; Àz þ 1 2 .…”
Section: Related Literaturementioning
confidence: 99%